Polypeptide Expression in Prostate Hyperplasia and Prostate Adenocarcinoma - Ayodele Alaiya; Uwe Roblick; Lars Egevad; Adelaide Carlsson; Bo Franzén; Daniela Volz; Sören Huwendiek; Stig Linder; Gert Auer (Analytical Cellular Pathology)
Cells were collected from prostate hyperplasias (n=6) and prostate carcinomas (n=6) and subjected to two‐dimensional gel electrophoresis (2‐DE). The resulting polypeptide patterns were analysed with the PDQUEST computer software. Malignant tumors showed significant increases in the level of expression of proliferating cell nuclear antigen (PCNA), calreticulin, HSP 90 and pHSP 60, oncoprotein 18(v), elongation factor 2, glutathione‐S‐transferase π (GST‐π), superoxide dismutase and triose phosphate isomerase. In addition, decreases in the levels of tropomyosin‐1 and 2 and cytokeratin 18 were observed in prostate carcinomas compared to prostate hyperplasias. This pattern of alterations is similar to that observed in other carcinomas in our previous studies. All malignant tumors showed simultaneous alterations in 5 or more of 9 markers studied, whereas only one case of benign hyperplasia showed alterations in 5 markers. The EST‐data base for prostate tumors available from NCI (CGAP) was searched for the expression of the mRNAs corresponding to proteins identified in our gels. Large differences in the relative expression of mRNAs and proteins were observed. Our data show alterations in the pattern of polypeptide expression in prostate carcinomas which are similar to those observed in other carcinomas.